Photoreactivity of Oil and Alcoholic Diterpenic Varnishes: Key Role of the Polymerization Process - Azémard, Clara (2020)
he conservation of artworks is a key issue in cultural heritage. The alterations of the varnish could be linked mainly to the photopolymerization of the natural resin. The photodegrada- tion of sandarac and rosin under simulated solar light was studied using a multianalytical approach using a second derivative FT-IR spectroscopy and gas chromatography coupled to mass spectroscopy. In all resins, main terpene molecules underwent esterification and perestererifications via the for- mation of hydroperoxides preferentially formed on tertiary carbons. This polymerization could be associated with the advice of important art manuals and treatises recommending exposing varnishes to the sunlight while drying. In a second step, these esters and perester bonds underwent photo- scissions by Norrish I and II reactions, leading to the production of free terpenes in the varnishes. In sandarac varnishes, the vinyl bonds showed a strong reactivity associated with the formation of trans and cis secondary alkenes. These photo- chemical reactions could explain an important part of the problem of conservation of the varnish layers experienced by museums all over the world.